Influenza-associated mortality in 2009 in four sentinel sites in Bangladesh - Nusrat Homaira; Stephen P Luby; ASM Alamgir; Kariul Islam; Repon Paul; Jaynal Abedin; Mustafizur Rahman; Tasnim Azim; Goutam Podder; Badrul Munir Sohel; Abdullah Brooks; Alicia M Fry; et al. (Bulletin of the World Health Organization, 2012)
OBJECTIVE: To estimate influenza-associated mortality in Bangladesh in 2009. METHODS: In four hospitals in Bangladesh, respiratory samples were collected twice a month throughout 2009 from inpatients aged <5 years with severe pneumonia and from older inpatients with severe acute respiratory infection. The samples were tested for influenza virus ribonucleic acid (RNA) using polymerase chain reaction. The deaths in 2009 in five randomly selected unions (the smallest administrative units in Bangladesh) in each hospital's catchment area were then investigated using formal records and informal group discussions. The deaths of those who had reportedly died within 14 days of suddenly developing fever with cough and/or a sore throat were assumed to be influenza-associated. The rate of such deaths in 2009 in each of the catchment areas was then estimated from the number of apparently influenza-associated deaths in the sampled unions, the proportion of the sampled inpatients in the local hospital who tested positive for influenza virus RNA, and the estimated number of residents of the sampled unions. FINDINGS: Of the 2500 people known to have died in 2009 in all 20 study unions, 346 (14%) reportedly had fever with cough and/or sore throat within 14 days of their deaths. The estimated mean annual influenza-associated mortality in these unions was 11 per 100000 population: 1.5, 4.0 and 125 deaths per 100000 among those aged <5, 5-59 and >59 years, respectively. CONCLUSION: The highest burden of influenza-associated mortality in Bangladesh in 2009 was among the elderly.